Analisis Kesantunan dan Tindak Tutur Masyarakat (Komunitas Ojol) - Aura Salvia Siregar; Dea Bilqis Ananda Br Sinaga; Putri Fadillah; Arief Sholeiman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to analyze the Politeness and Speech Acts of the Community (Ojol Community). This research uses a qualitative approach with descriptive method. Data were obtained through direct observation and recording of conversations between online ojek drivers and customers in real situations. Recording is done naturally without intervention to reflect authentic speech acts. The audio data is then transcribed and analyzed using Searle's speech act theory. The analysis is done descriptively qualitative by classifying and interpreting the form and function of utterances in the context of the conversation. The results show that nonstandard language is more dominantly used in informal communication, such as conversations between online ojek drivers and passengers, because it is considered more familiar, relaxed, and efficient. However, mastery of standardized language is still important, especially in official contexts, to maintain clarity and politeness. People are expected to be able to adjust the use of language according to the context so that communication remains effective and in accordance with linguistic norms. Keywords: , , , , .